Mediasi Penal Sebagai Alternatif Penyelesaian Perkara Pidana Di Luar Pengadilan - Faisal (PRANATA HUKUM, 2011)
Victim-offender mediation (VOM) is one of the penal mediation models used to settle the criminal cases. The origin of Victim-offender mediation was influenced by tribal moots model, unefisiency of criminal justice system, and restorative justice principles. Victim-offender mediation (VOM) is alternative dispute resolution with criminal case special, to see through criminal case between victim and crimnal actor:Â mediation tries to place offender and victim as a part of criminal justice system. Generally, Victim-offender mediation is dealing with the property offences, libel, offences against race, religion, and sexual harrasment. Victim-offender mediation also involves four fases of mediation, in take, confrontation, mediation its self, and outward. As the mediation model, Victim-offender mediation has the weaknesses and strenghs for offender, victim and society.